Mamluk Cultural Heritage and Sustainable Tourism: The Interplay of Heritage Value, Cultural Identity, and Behavioral Intentions in Promoting Roots Tourism - Ahmed Mohammed, Mamdouh; Ahmed , Hebatallah; Abdelal Sultan, Gihan; Abdelhai Abdelghani, Abdelrahman Ahmed (Cultural Arts Research and Development, 2024)
This study examines the interplay between heritage value, cultural identity, and behavioral intentions in promoting sustainable roots tourism associated with Egypt’s Mamluk cultural heritage. While scholarly attention has predominantly focused on Egypt’s Pharaonic legacy, Mamluk-era sites (13th–16th centuries)—noted for their synthesis of Islamic architecture and geopolitical significance—remain understudied despite their potential for diaspora engagement. Employing the Theory of Planned Behavior (TPB), this research adopts a quantitative approach to analyze survey responses from 215 international visitors with ancestral ties to Mamluk-linked regions (Central Asia, the Caucasus, and Turkey). Regression analysis explained 62.3% of the variance in sustainable tourism intentions (R² = 0.623). Results revealed strong positive relationships among cultural heritage value (*r* = 0.730), cultural identity (*r* = 0.697), and sustainable behavioral intentions. Architectural aesthetics (M = 4.43/5) and emotional identity (M = 4.28/5) emerged as significant predictors, though perceived behavioral control (M = 3.98/5) suggested logistical barriers. The findings underscore the need for immersive storytelling, community-centered strategies, and policy reforms to enhance visitor experiences and preservation outcomes. This study promotes theoretical and practical approaches to sustainable tourism by integrating TPB with frameworks of historical values, so that Mamluk sites can be established as agents of socio-economic flexibility and cultural diplomacy. Limitations include the cross-sectional design and sampling focus, warranting longitudinal studies with broader demographic inclusion.